2007
DOI: 10.1037/cjbs2007001
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric properties of the Early Development Instrument (EDI): A measure of children's school readiness.

Abstract: The Early Development Instrument (EDI), a teacher-completed measure of children's school readiness at entry to Grade 1, was designed to provide communities with an informative, inexpensive and psychometrically sound tool to assess outcomes of early development as reflected in children's school readiness. Its psychometric properties at individual level were evaluated in two studies. Five a priori domains -physical health and well-being, social competence, emotional maturity, language and communication, and cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
529
2
20

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 533 publications
(559 citation statements)
references
References 60 publications
8
529
2
20
Order By: Relevance
“…Teacher ratings of children's DB and school adjustment were based on the Self-Administered Questionnaire for Teacher (SAQT; Lemelin & Boivin, 2007), completed at the end of first grade. The SAQT is a 163-item questionnaire based on the Early Development Instrument (EDI; Janus and Offord, 2007), which assesses teachers' perceptions of children's school readiness at the end of kindergarten. The SAQT was adapted to correspond to the level of development of first graders, by removing inappropriate items (e.g., referring to language and cognitive skills typically preceding school entry) and by adding others (e.g., referring to advanced skills and to academic performance) drawn from the National Longitudinal Study of Children and Youth (NLSCY;Statistics Canada, 1995).…”
Section: Teacher's Assessment Of Db and School Impairment In First Gradementioning
confidence: 99%
“…Teacher ratings of children's DB and school adjustment were based on the Self-Administered Questionnaire for Teacher (SAQT; Lemelin & Boivin, 2007), completed at the end of first grade. The SAQT is a 163-item questionnaire based on the Early Development Instrument (EDI; Janus and Offord, 2007), which assesses teachers' perceptions of children's school readiness at the end of kindergarten. The SAQT was adapted to correspond to the level of development of first graders, by removing inappropriate items (e.g., referring to language and cognitive skills typically preceding school entry) and by adding others (e.g., referring to advanced skills and to academic performance) drawn from the National Longitudinal Study of Children and Youth (NLSCY;Statistics Canada, 1995).…”
Section: Teacher's Assessment Of Db and School Impairment In First Gradementioning
confidence: 99%
“…A growing number of studies have established that the EDI has good internal and test-retest reliability as well as external validity (Forget-Dubois et al 2007;Janus and Offord 2007;Forer and Zumbo 2011;Guhn and Goelman 2011;Hymel, Le Mare, and McKee 2011;Janus, Brinkman, and Duku 2011). Early studies of the instrument indicated that: 'The EDI's psychometric properties have proven to be acceptable' (Janus and Offord 2007, 18;).…”
Section: Outcome Variablesmentioning
confidence: 99%
“…Recently, many place-based efforts have taken a life course approach in attempt to improve cradle-to-career trajectories with attention paid to what works in different kinds of communities and microenvironments. Community-based researchers in Canada have used a new set of measures including the Early Development Instrument (administered from ages 4-6 years) and the Middle Development Instrument (administered at ages 9-11 years) to collect developmentally and dimensionally consistent measures of health development (Janus and Offord 2007;Schonert-Reichl et al 2013). This life course-oriented population data collection can be used to map and track health and well-being at different developmental stages, and to engage community members in identifying early development outcomes and how they relate with local community services and risk and protective factors, and in turn developing action strategies for systems-and community-level improvements.…”
Section: Research Prioritiesmentioning
confidence: 99%